min ( y ) \min (y)

Algebra Level 3

y = 5 x 2 + 2 x 5 + 1 + x 5 \large y=\sqrt{5x^2+2x\sqrt{5}+1}+x\sqrt{5}

Find the minimum value of y y .


The answer is -1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Michael Mendrin
Aug 2, 2018

Make the substitution x = z x=-z to get

y = ( z 5 + 1 ) 2 z 5 y=\sqrt{(-z\sqrt{5}+1)^2}-z\sqrt{5}

y = ( z 5 1 ) 2 z 5 y=\sqrt{(z\sqrt{5}-1)^2}-z\sqrt{5}

y = ( z 5 1 ) z 5 y=(z\sqrt{5}-1)-z\sqrt{5} for z 5 1 z\sqrt{5} \ge 1

y = 1 y=-1 for x 1 5 x \le -\dfrac{1}{\sqrt{5}}

Given that

y = 5 x 2 + 2 x 5 + 1 + x 5 = ( x 5 + 1 ) 2 + x 5 \begin{aligned} y & = \sqrt{5x^2+2x\sqrt 5+1} + x\sqrt 5 \\ & = \sqrt{({\color{#3D99F6}x\sqrt 5+1})^2} + x\sqrt 5 \end{aligned}

For y y to be real, x 5 + 1 0 \color{#3D99F6}x\sqrt 5 + 1 \ge 0 , x 1 5 \implies x \ge - \frac 1{\sqrt 5} and y y is minimum when x = 1 5 x = - \frac 1{\sqrt 5} that is min ( y ) = 0 + ( 1 5 ) 5 = 1 \min(y) = \sqrt 0 + \left(-\frac 1{\sqrt 5}\right) \sqrt 5 = \boxed{-1} .

Jamar Sullivan
Jul 21, 2019

I did a long-winded calculus approach so bare with me!

Since we are trying to find the minimum value, we know that we can find the derivative of the function and find where it is equal to zero

y = 5 x 2 + 2 x 5 + 1 + x 5 y = \sqrt{5x^{2}+2x\sqrt{5}+1}+x\sqrt{5}

d y d x = 10 x + 2 5 2 5 x 2 + 2 x 5 + 1 + 5 = 5 x + 5 5 x 2 + 2 x 5 + 1 + 5 \frac{dy}{dx}=\frac{10x+2\sqrt{5}}{2\sqrt{5x^{2}+2x\sqrt{5}+1}}+\sqrt{5} = \frac{5x+\sqrt{5}}{\sqrt{5x^{2}+2x\sqrt{5}+1}}+\sqrt{5}

Now if we set it equal to zero, and using some algebra...

5 x + 5 5 x 2 + 2 x 5 + 1 + 5 = 0 \frac{5x+\sqrt{5}}{\sqrt{5x^{2}+2x\sqrt{5}+1}}+\sqrt{5} = 0

5 x + 5 5 x 2 + 2 x 5 + 1 = 5 \frac{5x+\sqrt{5}}{\sqrt{5x^{2}+2x\sqrt{5}+1}} = -\sqrt{5}

5 x + 5 = 5 5 x 2 + 2 x 5 + 1 5x+\sqrt{5} = -\sqrt{5}\sqrt{5x^{2}+2x\sqrt{5}+1}

5 x + 5 = 5 ( 5 x 2 + 2 x 5 + 1 ) 5x+\sqrt{5} = -\sqrt{5(5x^{2}+2x\sqrt{5}+1)}

5 x + 5 = 25 x 2 + 10 x 5 + 5 5x+\sqrt{5} = -\sqrt{25x^{2}+10x\sqrt{5}+5}

5 x + 5 = ( 5 x + 5 ) 2 5x+\sqrt{5} = -\sqrt{( 5x+\sqrt{5})^{2}}

5 x + 5 = 5 x 5 5x+\sqrt{5} = -5x-\sqrt{5}

Solving for x, we get... x = 5 5 x = \frac{-\sqrt{5}}{5}

Finally, we just have to plug it into the original equation, and we get

y = 5 ( 5 5 ) 2 + 2 ( 5 5 ) 5 + 1 + ( 5 5 ) 5 y = \sqrt{5(\frac{-\sqrt{5}}{5})^{2}+2(\frac{-\sqrt{5}}{5})\sqrt{5}+1}+(\frac{-\sqrt{5}}{5})\sqrt{5}

y = 0 + ( 5 5 ) 5 y = 0 + (\frac{-\sqrt{5}}{5})\sqrt{5} )

y = 1 y = \boxed{-1}

Feedback is always appreciated!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...